2010
DOI: 10.1002/esp.1970
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary evidence of Late Holocene human activity in the Pearl River delta, China

Abstract: This study examines the sedimentary evidence of human activities during the last 4000 years in the Pearl River deltaic area. The analyses are focused on indentifying agricultural signatures present in the sedimentary record and establishing the timing of a change from a simple, rice-based agriculture to a more advanced, diverse agriculture. The examination is based on modern sediment and plant samples and a sediment core collected from the deltaic area. The analyses include particle size and diatom analysis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 21 publications
6
50
0
Order By: Relevance
“…The radiocarbon date from 0.52 m produced a modern age (108 cal yr BP), while the date from 1.33 m (immediately below the boundary between zones 1 and 2) provided an age of 2337 -2162 cal yr BP. Based on the chronology and clear change in character of the sediments the change from Zone 1 to Zone 2 most likely relates to enhanced human activity in this area as discussed by Zong et al (2010c). In this paper we concentrate on the mid-Holocene section preserved in Zone 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiocarbon date from 0.52 m produced a modern age (108 cal yr BP), while the date from 1.33 m (immediately below the boundary between zones 1 and 2) provided an age of 2337 -2162 cal yr BP. Based on the chronology and clear change in character of the sediments the change from Zone 1 to Zone 2 most likely relates to enhanced human activity in this area as discussed by Zong et al (2010c). In this paper we concentrate on the mid-Holocene section preserved in Zone 1.…”
Section: Resultsmentioning
confidence: 99%
“…The sedimentation environment was stable because particle size analysis shows no major change in sand, silt or clay fractions (Zong et al, 2010c), and there is no bioclastic storm bed found in this sediment section (eg Huang and Yim, 2001). The only thin sandy layer found in the core is located at 1.0 m (Zong et al, 2010c). Diatom assemblages from the section containing the age inversion show no significant change either (Zong et al, 2010b).…”
Section: Methodsmentioning
confidence: 92%
“…Liu and Huang, 2005), cave speleothems (e.g. Dong et al, 2010;Wang et al, 2005;Zhang et al, 2004) and organic matter flux (Yu et al, 2012;Zong et al, 2006;Zong et al, 2010). Overall, these datasets indicate a general decline in precipitation across Asia from 6.5 ka to present.…”
Section: Introductionmentioning
confidence: 80%
“…This sample is from a region of the core that has been previously attributed to a marine storm event associated with significant marine deposition (Yu, 2009;Zong et al, 2010).…”
Section: Bit Indicesmentioning
confidence: 99%
See 1 more Smart Citation